propuesta desde el tratamiento integrado de las lenguas (TIL): la entrevista en la ESO - Ugalde Ustárroz, Nerea (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
The aim of this article is to show, through a didactic sequence, how two languages can be taught at the same time. In these pages I introduce a didactic programme to approach the genre of the interview in both the mother tongue and in English as a foreign language in third of E.S.O. As the Navarra’s curricula indicates, this type of text has to be studied at Secondary schools in both languages. Therefore, my objective is to present a didactic proposal which enables students to improve and maximise their integrated language learning and develop their bilingual communicative skills.